2002
DOI: 10.1073/pnas.152324199
|View full text |Cite
|
Sign up to set email alerts
|

An anatomy of normal and malignant gene expression

Abstract: A gene's expression pattern provides clues to its role in normal physiology and disease. To provide quantitative expression levels on a genome-wide scale, the Cancer Genome Anatomy Project (CGAP) uses serial analysis of gene expression (SAGE). Over 5 million transcript tags from more than 100 human cell types have been assembled. To enhance the utility of this data, the CGAP SAGE project created SAGE Genie, a web site for the analysis and presentation of SAGE data (http:͞͞cgap.nci.nih.gov͞SAGE). SAGE Genie pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
227
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 273 publications
(237 citation statements)
references
References 15 publications
5
227
0
Order By: Relevance
“…Symplekin expression in human colorectal cancer (CRC) was analyzed in the SAGE Genie database (16), which indicated that symplekin mRNA identification tags are strongly overexpressed in human tumors from the colon, lung, muscle, and prostate, compared with healthy tissue (http://cgap.nci.nih.gov/SAGE). Using RTqPCR, we found that the symplekin mRNA was overexpressed in ∼67% (8/12) CRC tumor samples compared with matching healthy tissue, without any obvious correlation with tumor stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Symplekin expression in human colorectal cancer (CRC) was analyzed in the SAGE Genie database (16), which indicated that symplekin mRNA identification tags are strongly overexpressed in human tumors from the colon, lung, muscle, and prostate, compared with healthy tissue (http://cgap.nci.nih.gov/SAGE). Using RTqPCR, we found that the symplekin mRNA was overexpressed in ∼67% (8/12) CRC tumor samples compared with matching healthy tissue, without any obvious correlation with tumor stage (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such estimations are supported by improved gene discovery. For instance, the standard cerebellum library 15 shows ∼2.5% of unique clusters versus ∼10% of the subtracted library A7 ( Although such estimations should be verified experimentally, this approach seems to provide a coverage that is not inferior to SAGE, for which there are currently more than 6,000,000 tags in current databases (Boon et al 2002).…”
Section: Coveragementioning
confidence: 90%
“…Serial analysis of gene expression (SAGE) allows quantitative characterization and has the added value over microarray expression profiling in its ability to identify novel splice variants, exons, and genes [22][23][24]. Since SAGE libraries comprise discrete data, they can be subjected to pairwise comparison to statistically analyze the differential expression of genes [25] and to generate a comparative digital gene expression profile [24].…”
Section: Introductionmentioning
confidence: 99%